2012
DOI: 10.1007/s10620-012-2376-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prognosis of Pulmonary Complications After Endoscopic Submucosal Dissection for Gastric Neoplasia

Abstract: Deep sedation under continuous propofol infusion with opioid injection during ESD may be a risk factor for pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 25 publications
2
62
4
Order By: Relevance
“…Our findings were consistent with those of many past reports. However, aspiration pneumonia was more frequent in our study (11.2% of patients) than that reported in previous studies [8,16,17,18]. For instance, Akasaka et al [8] reported that aspiration pneumonia after ESD occurred in 1.6% of patients.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Our findings were consistent with those of many past reports. However, aspiration pneumonia was more frequent in our study (11.2% of patients) than that reported in previous studies [8,16,17,18]. For instance, Akasaka et al [8] reported that aspiration pneumonia after ESD occurred in 1.6% of patients.…”
Section: Discussioncontrasting
confidence: 70%
“…In their study, chest radiography was performed in cases in which an attending physician suspected postoperative pneumonia based on the clinical symptoms. In addition, Park et al [17] reported that aspiration pneumonia developed in approximately 2.3% of patients. The authors reported that, of all the patients who underwent chest radiography on the day preceding ESD and a day after ESD, 1.1% presented lung consolidation on chest radiography without respiratory signs or symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when respiratory depression or unrest occurs with midazolam, the administration of an early dose of flumazenil should be carefully considered. Indeed, continuous propofol infusions with the administration of an opioid and a patient age of over 75 years are independent risk factors for pneumonia after ESD (20). Deterioration of the performance status also increases the risk of aspiration pneumonia after ESD (21).…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration of the performance status also increases the risk of aspiration pneumonia after ESD (21). In a retrospective study (20), 56 of 1,661 patients were diagnosed with pneumonia after ESD. In the present study, none of the elderly patients developed pneumonia, although oxygen administration was required in 57.6% of the cases.…”
Section: Discussionmentioning
confidence: 99%